An Empirical Study of Factors Affecting Accounting Students' Career Choice in New Zealand - Ahmed, Kamran; Alam, Kazi Feroz; Alam, Manzurul (School of Management Working Papers, 1996)
The study examines the influence of intrinsic factors; financial and job-related factors; other factors such as parent and peer influence, and work experience; exposure to high school accounting; and the students' perceived benefit-cost ratio on whether accounting students choose to pursue a chartered accounting (CA) career or not. Based on a survey of 295 students from five universities in New Zealand, the results show that the students who intend to pursue a CA career place significantly greater importance on financial and job-related factors, and perceived benefit-cost ratio than those who choose a non-accounting career. Intrinsic factors, other factors and exposure to high school accounting have no significant influence on the decisions whether to select a career in CA. A discriminant analysis revealed that financial and job-related factors have the highest explanatory power differentiating the two groups, followed by the students' perception of benefits and costs associated with a CA career. The results have important implications for recruitment into the accounting profession.